Analisis Capaian Pembangunan Inklusif Hijau Pada Tingkat Kabupaten/Kota Di Jawa Timur dengan Balanced Inclussive Green Growth Index - Purwanti, Yuniasih; Dianzah, Yoshi Evlyn Nathania (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2023)
Growth development is a multidimensional process that includes economic growth, the level of social welfare and environmental quality. This study aims to measure the achievement of balanced green economy inclusive growth at the district/city level in East Java in 2018 and 2021 using the concept of the Balance Inclusive Green Growth Index (BIGGI). Based on the results of the analysis conducted, it shows that the results of the BIGGI index in East Java are quite even. In general, the entire region of East Java has a high social dimension, except for districts on Madura Island. As for urban areas and industrial centers, BIGGI's achievements are influenced by the high value of the economic and social dimensions, but followed by the low value of the environmental dimension. The low value of the environmental dimension also affects the BIGGI pro forma imbalance in urban areas, where the BIGGI value is lower than the IGGI.